Office-Based Surgical and Medical Procedures: Educational Gaps - Urman, Richard D. (the Academic Division of Ochsner Clinic Foundation, 2012)
Over the past decade, the number of procedures performed in office-based settings by a variety of practitioners—including surgeons, gastroenterologists, ophthalmologists, radiologists, dermatologists, and others—has grown significantly. At the same time, patient safety concerns have intensified and include issues such as proper patient selection, safe sedation practices, maintenance of facilities and resuscitation equipment, facility accreditation and practitioner licensing, and the office staff's ability to deal with emergencies and complications. An urgent need exists to educate practitioners about safety concerns in the office-based setting and to develop various educational strategies that can meet the continued growth of these procedures. This review outlines educational needs and possible solutions such as simulation exercises and education during residency training.